2019
DOI: 10.3847/1538-4357/ab4b50
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostics of the Prominence Plasma from Hα and Mg ii Spectral Observations

Abstract: The goal of this paper is to derive the physical conditions of the prominence observed on 2017 March 30. To do so, we use a unique set of data in Mg II lines obtained with the space-borne Interface Region Imaging Spectrograph (IRIS) and in Hα line with the ground-based Multi-Channel Subtractive Double Pass spectrograph operating at the Meudon solar tower. Here, we analyze the prominence spectra of Mg II h and k lines, and the Hα line in the part of the prominence which is visible in both sets of lines. We comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…This issue is seen when attempting direct one-dimensional forward modelling of Hα prominences. For example, Ruan et al (2019) demonstrated that areas with wide Hα line profiles can be better fit by models with high microturbulent velocities. Whether this is also true for Mg ii line profiles is currently unclear.…”
Section: Resultsmentioning
confidence: 99%
“…This issue is seen when attempting direct one-dimensional forward modelling of Hα prominences. For example, Ruan et al (2019) demonstrated that areas with wide Hα line profiles can be better fit by models with high microturbulent velocities. Whether this is also true for Mg ii line profiles is currently unclear.…”
Section: Resultsmentioning
confidence: 99%
“…integrated intensity and FWHM of Mg ii and Hα lines in each pixel, the second method is based on the fitting of Mg ii h and k line profiles with synthesised profiles using the radiative transfer code. The first method has already been used in previous studies of prominences (Wiik et al 1992;Heinzel et al 2015;Jejčič et al 2018;Ruan et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The broad profiles could also be due to high microturbulence. In Ruan et al (2019) paper, high micro turbulence was used as a proxy of multi structure velocities. A 2D NLTE radiative model would be suitable to fit more profiles with wide FWHM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations